Radioprotectant and Cytotoxic Effects of Spirulina in Relapsed Verrucous Vulvar Cancer: A Case Report - KIZILTAN, HURİYE ŞENAY; Kiziltan, HURİYE ŞENAY; GÜNEŞ BAYIR, AYŞE; Bayir, Ayse Gunes; YÜCESAN, GÜL; TAŞPINAR, Ozgur; ÇOBAN, GANİME; Yucesan, GÜL; KILIC, GÖKHAN; Tastekin, Didem; ERİŞ, ALİ HİKMET; SONMEZ, Fatma Cavidan; et al. (My University, 2015)
Context . The treatment of relapsed verrucous vulvar cancer (VVC) is difficult. When vulvar cancer relapses, the treatment response is low for second-line treatments. Conversely, toxicity is high. Therefore, scientists need to identify different treatment methods.